Using tablets to support self-regulated learning in a longitudinal integrated clerkship - Dylan Archbold Hufty Alegría; Christy Boscardin; Ann Poncelet; Chandler Mayfield; Maria Wamsley (Medical Education Online, 2014)
Introduction: The need to train physicians committed to learning throughout their careers has prompted medical schools to encourage the development and practice of self-regulated learning by students. Longitudinal integrated clerkships (LICs) require students to exercise self-regulated learning skills. As mobile tools, tablets can potentially support self-regulation among LIC students. Methods: We provided 15 LIC students with tablet computers with access to the electronic health record (EHR), to track their patient cohort, and a multiplatform online notebook, to support documentation and retrieval of self-identified clinical learning issues. Students received a 1-hour workshop on the relevant features of the tablet and online notebook. Two focus groups with the students were used to evaluate the program, one early and one late in the year and were coded by two raters. Results: Students used the tablet to support their self-regulated learning in ways that were unique to their learning styles and increased access to resources and utilization of down-time. Students who used the tablet to self-monitor and target learning demonstrated the utility of tablets as learning tools. Conclusions: LICs are environments rich in opportunity for self-regulated learning. Tablets can enhance students’ ability to develop and employ self-regulatory skills in a clinical context.